2016
DOI: 10.1038/srep31782
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the performance of pooled CRISPR–Cas9 drop-out screening

Abstract: Components of the type II CRISPR–Cas complex in bacteria have been used successfully in eukaryotic cells to facilitate rapid and accurate cell line engineering, animal model generation and functional genomic screens. Such developments are providing new opportunities for drug target identification and validation, particularly with the application of pooled genetic screening. As CRISPR–Cas is a relatively new genetic screening tool, it is important to assess its functionality in a number of different cell lines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 19 publications
0
33
0
Order By: Relevance
“…One approach is to optimise the gRNA scaffold sequences. Several studies have been conducted thus far and resulted in a similar structure, which showed more robust phenotypic outcomes 38 , 45 , 46 . Another approach is to computationally predict on-target efficiency using nucleotide biases on gRNA KO efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…One approach is to optimise the gRNA scaffold sequences. Several studies have been conducted thus far and resulted in a similar structure, which showed more robust phenotypic outcomes 38 , 45 , 46 . Another approach is to computationally predict on-target efficiency using nucleotide biases on gRNA KO efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, CRISPRi appears to be a more sensitive technique than CRISPRko, indicated by the substantially improved detection for MED12 and MED23 in both screens. Some of this increase in sensitivity is likely to be due to the use of an improved tracrRNA sequence 29 in the CRISPRi vector, which was not used in the CRISPRko screen (Figure S1 ). At the guide level, the increased sensitivity for both MED12 and MED23 might also be attributable to the fact that all 5 guides are active and therefore substantially enriched in the screen, whereas for other potential hits, such as NF1, fewer guides appear to be active (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To expand on our 3Cs technology and enable Cas9 gRNA multiplexing, we generated a lentiviral Cas9-gRNA expression plasmid (pLenti-Multiplex) by placing a human 7SK (h7SK) promoter upstream of a previously engineered Cas9-tracrRNA followed by a human U6 (hU6) promoter upstream of a wildtype Cas9-tracrRNA sequence 46,47 . Both gRNA cassettes contain a gRNA placeholder sequence encoding for I-CeuI or I-SceI restriction enzyme sites, respectively ( Figure 1A) 45 .…”
Section: Results 3cs Multiplexed Cas9 Grna Librariesmentioning
confidence: 99%